Payday Loans and Credit Cards: New Liquidity and Credit Scoring Puzzles? - Agarwal, Sumit; Skiba, Paige Marta; Tobacman, Jeremy (American Economic Review, 2009)
Payday Loans and Credit Cards: New Liquidity and Credit Scoring Puzzles? by Sumit Agarwal, Paige Marta Skiba and Jeremy Tobacman. Published in volume 99, issue 2, pages 412-17 of American Economic Review, May 2009